2013
DOI: 10.1073/pnas.1313893110
|View full text |Cite
|
Sign up to set email alerts
|

Development of a histone deacetylase 6 inhibitor and its biological effects

Abstract: Development of isoform-selective histone deacetylase (HDAC) inhibitors is important in elucidating the function of individual HDAC enzymes and their potential as therapeutic agents. Among the eleven zinc-dependent HDACs in humans, HDAC6 is structurally and functionally unique. Here, we show that a hydroxamic acid-based small-molecule N-hydroxy-4-(2-[(2-hydroxyethyl)(phenyl)amino]-2-oxoethyl)benzamide (HPOB) selectively inhibits HDAC6 catalytic activity in vivo and in vitro. HPOB causes growth inhibition of nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 27 publications
(46 reference statements)
1
105
0
1
Order By: Relevance
“…13 While confirming the activity of 17-AAG as such, we observed only minor synergistic effects of Tubacin and 17-AAG on UC cell lines, independent of their HDAC6 expression levels. Similarly, treatment with Tubacin did not enhance the sensitivity of UC cells to the DNA-damaging anticancer drugs doxorubicin and etoposide, unlike glioblastoma, prostate, mammary, and lung cancer cell lines 23,24 . The minor effects would not allow to reduce concentrations to a minimum that could be administered in the clinic.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…13 While confirming the activity of 17-AAG as such, we observed only minor synergistic effects of Tubacin and 17-AAG on UC cell lines, independent of their HDAC6 expression levels. Similarly, treatment with Tubacin did not enhance the sensitivity of UC cells to the DNA-damaging anticancer drugs doxorubicin and etoposide, unlike glioblastoma, prostate, mammary, and lung cancer cell lines 23,24 . The minor effects would not allow to reduce concentrations to a minimum that could be administered in the clinic.…”
Section: Discussionmentioning
confidence: 87%
“…Newly developed compound as such as HPOB or C1A are however reported to be selective for HDAC6 compared with HDAC10. 24,51 Subsequently, we compared the three compounds regarding their effects on the viability of urothelial cancer cell lines. In parallel with the data on the molecular effects, ST-80 appeared as the least potent compound with little efficacy even at high micromolar concentrations (100 μM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 HDAC6, a class IIb enzyme, is structurally and functionally unique among the eleven human zinc-dependent HDACs. 6 It is the only HDAC with two independent functional catalytic domains and a C-terminal zinc finger motif responsible for binding ubiquitinated proteins. 5b Interestingly, it has been demonstrated that the second catalytic site is the major functional domain of HDAC6.…”
mentioning
confidence: 99%
“…Histone deacetylase enzymatic activity was assayed as previously described (3). In vitro activities of the 11 recombinant human zinc-dependent HDAC enzymes (BPS Biosciences) were detected by fluorigenic release of 7-amino-4-methylcoumarin from substrate upon deacetylase enzymatic activity.…”
Section: Methodsmentioning
confidence: 99%